Rethinking Socialization Research through the Lens of New Materialism - Höppner, Grit (Frontiers in Sociology, 2017)
In recent decades, socialization research appears to have suffered the loss of its former capacity to explain the processes of becoming a socialized subject in a social environment. In this article I review socialization theories taking into account assumptions regarding human subjects and their social environments. I confront them with the idea of rethinking dualisms, ontologies and agencies addressed by the field of new materialism. I propose a new materialist-inspired socialization theory that assumes that humans, knowledge, and material environments become inseparable parts of (gendered) socialization processes in a world of constant change. This approach contributes to socialization theory and methodology because it illustrates precisely how humans and non-humans co-produce socialization in situated material-discursive processes.